How to Optimize Deimplementation of Sentinel Lymph Node Biopsy? - Ida Dragvoll; Anna M. Bofin; Håvard Søiland; Monica Jernberg Engstrøm (Hindawi-Wiley, 2024)
Background. The omission of sentinel lymph node biopsy in low-risk elderly breast cancer patients has been introduced in several guidelines. Despite evidence to support its safety, this recommendation has not been implemented by many clinicians. We have examined two aspects of this recommendation that may explain why sentinel lymph node biopsy continues to be performed in most of these patients. Firstly, we quantified the proportion of patients diagnosed with axillary metastases postoperatively. Secondly, we examined adherence to antihormonal therapy in the same group of patients. Methods. In this single-centre retrospective cohort study, the study population comprised 98 patients with breast cancer. Patients were aged ≥70 years and diagnosed with hormone receptor positive breast cancers less than 20 mm (T1). All patients underwent surgery and were subsequently prescribed five years of adjuvant antihormonal treatment. Results. Axillary lymph node metastases, as confirmed by the postoperative histology report, were seen in 36.3%. Nonadherence was seen in 33.7% of the patients. Primary nonadherence, that is, patients that never collect their first or subsequent prescriptions at the pharmacy, comprised 11.2% of the total study population. Conclusion. The high proportion of axillary metastases demonstrated suggests that clinical examination of the axilla alone is not sufficient in the preoperative assessment of the axilla. The less-than-optimal adherence rates show that adherence in these patients cannot be taken for granted. We suggest that these factors reflect some of the reluctance among clinicians to omit the sentinel lymph node procedure in these patients.